PLACES OF POVERTY, PLACES OF SEPARATION (PANGEEA, 2025)
ABSTRACT: The plaţ is a word frequently found in the stories of the Roma who beg abroad. The term became more and more present in their speech as the begging phenomenon expanded and the number of persons requesting public pity in Western countries increased. The plaţurile (plural form, author’s note) are empty or marginal sites in (large) West-European urban centres, where the Roma placed tents or caravans for residence. Separate from the areas inhabited by the locals, the plaţurile are territorial units as well as settlements specific to the Roma immigrants’ culture.
Keywords: plaţ; campi nomadi; places; Roma; segregation